2014
DOI: 10.3109/08880018.2014.987938
|View full text |Cite
|
Sign up to set email alerts
|

Seeking a Second Opinion in Pediatric Oncology

Abstract: Second opinion consultations were not uncommon and were mainly secondary to the desire for reassurance. Pediatric oncologists should ensure that patients and their families feel comfortable requesting a second opinion consultation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…A third study found no relation with disease stage . Use of complementary and alternative medicine was related to more SO seeking among Chinese gynecological patients but not among parents of Israeli pediatric patients . Other medical characteristics correlated with SO seeking were treatment advice (breast cancer patients advised to have a mastectomy vs. breast‐conserving therapy more likely sought an SO) , and previous treatments undergone (gynecological cancer patients seeking an SO more likely had received radiotherapy) .…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…A third study found no relation with disease stage . Use of complementary and alternative medicine was related to more SO seeking among Chinese gynecological patients but not among parents of Israeli pediatric patients . Other medical characteristics correlated with SO seeking were treatment advice (breast cancer patients advised to have a mastectomy vs. breast‐conserving therapy more likely sought an SO) , and previous treatments undergone (gynecological cancer patients seeking an SO more likely had received radiotherapy) .…”
Section: Resultsmentioning
confidence: 94%
“…A third study found that SO seekers were more often non-blacks than blacks [32]. Place of residence was not predictive of SO seeking in one study [24], whereas another found that SO seekers were more often residents of non-central city metropolitan areas [20]. Finally, SO seeking was associated with higher familiarity with the medical system, more social support [29], and being non-religious [24].…”
Section: Sociodemographic Characteristicsmentioning
confidence: 93%
See 2 more Smart Citations
“…The demand for such active involvement in medical decisions progressively increased over the years [42,64]. Several studies suggest that about 68% of patients seek a second opinion, so that would get another diagnosis or prognosis, and 65% would assurance regarding the diagnosis or treatment options [44,47,[65][66][67]. Furthermore, the patients might seek another opinion to discuss their diagnosis and/or treatment, especially when they are dissatisfied with the first physician [45,47,63,65,68].…”
Section: Discussionmentioning
confidence: 99%